Implicações do sistema Professor Online para a gestão escolar no extremo oeste de Santa Catarina: uma discussão em políticas públicas para educação - Mueller, Sibele (2019)
The current research is inserted in the Educational Policies of the Post-Graduate Program of Master in Education in the Federal University of Fronteira Sul - UFFS. The study addresses a discussion about the implications of the Professor Online system in the educational management process, aproaching concepts about public policies, democratic school management and the use of information and communication technologies in the school environment. Therefore, the research application took place in the state public schools covered by the Education Management (GERED) of Itapiranga, Santa Catarina, guided by the study´s objective that consists in knowing the implications of the Professor Online system for the school management development in state public schools in the west of Santa Catarina. This work has a qualitative perspective, because it consists of data collection with teachers and school managers working in the schools belonging to the exposed context. The analysis of the collected data considered Bardin's categorization technique, where the results are presented and enriched with theoretical references, discussing them, in the light of public policies, considering the implications of the Professor Online system for the educational management process. As a result of the research, four categories related to the research's main points were evidenced: use of technological tools in the educational environment; educational management and its relationship to technology; observation and analysis of public policies and government initiatives in the state of Santa Catarina and general evaluation of the Professor Online system. Through the analysis of these categories it is highlighted the evolution and importance of the use of technologies in the school environment, the need for good use of these technologies in order to favor the actions performed in the education field, the advantage of having access to information provided by the Professor Online system, especially to monitor school activities and students' academic performance, which favors and contributes to democratic and collaborative management and the engagement of school community to improve the quality of the teaching process. It was also evidenced the difficulty related to public policies regarding the autonomy and participation of school community in their development process and the lack of financial resources for the application of public policies in education.